Replication Data for: Establishing common bean traits preferred by consumers in Uganda - asiimwe, robert (2022)
This dataset was collected in Uganda between November 2020 and February 2021. We collected data from over 1000 households across the major common bean-producing areas in Uganda. A discrete choice experiment approach was employed to elicit the preferences of common bean traits including cooking time and other attributes including grain swelling, taste, grain colour, climate resilience, and yield attributes of common beans. The data has been used to write and publish an article titled "Customer preference and demand for reduced cooking time and other traits in Ugandan bean markets: A choice experiment approach". The same data will be used to write and publish an article about perceptions of different common bean attributes and the role of gender in shaping these perceptions.